Diagnosis of Twisted Blade in Rotor System - M. H., Lim; W. K., Ngui (2015)
This paper studies the diagnosis of twisted blade in a multi-stages rotor system using vibration analysis. Experimental study was undertaken to simulate twisted blade conditions in a three stages rotor system. The feasibility of vibration analysis as the technique to detect twisted blade was investigated in this study. Vibration signals were analyzed with both Fourier and Wavelet transforms for comparison purposes. Experimental results showed that twisted blade can be detected by comparing the pattern in both the vibration spectrum and wavelet map. The feasibility and effectiveness of wavelet analysis as compared to vibration spectrum to detect twisted blade was also discussed and presented in this paper.